Determination of Molecular Diameter by PVT. (15th March 2012) - Moeini, Vahid; Deilam, Mehri
Abstract : We derive an equation for calculation of molecular diameter of dense fluids, with using simultaneous Lennard-Jones (12-6) potential function and the internal pressure results. Considering the internal pressure by modeling the average configurational potential energy and then taking its derivative with respect to volume to a minimum point of potential energy has been shown that molecular diameter is function of the resultant of the forces of attraction and the forces of repulsion between the molecules in a fluid. The regularity is tested with experimental data for 10 fluids including Ar, N2, CO, CO2, CH4, C2 H6, C3 H8, C4 H10, C6 H6, and C6 H5 CH3 . These problems have led us to try to establish a function for the accurate calculation of the molecular diameter based on the internal pressure theory for different fluids. The relationship appears to hold both compressed liquids and dense supercritical fluids.